2021
DOI: 10.3390/nu13092957
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals for the Control of Dyslipidaemias in Clinical Practice

Abstract: Dyslipidaemias result in the deposition of cholesterol and lipids in the walls of blood vessels, chronic inflammation and the formation of atherosclerotic plaques, which impede blood flow and (when they rupture) result in acute ischaemic episodes. Whilst recent years have seen enormous success in the reduction of cardiovascular risk using conventional pharmaceuticals, there is increasing interest amongst patients and practitioners in the use of nutraceuticals to combat dyslipidaemias and inflammation in cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…The unambiguous evidence supporting these therapies supports their continued (and expanding) role in risk reduction. In addition to these 'conventional' therapeutics, growing evidence supports the use of a range of 'nutraceuticals' (constituents of food prepared as pharmaceutical formulations) [11][12][13][14][15][16]. Efficacy claims have been made for a wide range of nutraceuticals in the CVD prevention and management.…”
Section: Lipids Lipoproteins and Atherosclerotic Cardiovascular Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…The unambiguous evidence supporting these therapies supports their continued (and expanding) role in risk reduction. In addition to these 'conventional' therapeutics, growing evidence supports the use of a range of 'nutraceuticals' (constituents of food prepared as pharmaceutical formulations) [11][12][13][14][15][16]. Efficacy claims have been made for a wide range of nutraceuticals in the CVD prevention and management.…”
Section: Lipids Lipoproteins and Atherosclerotic Cardiovascular Diseasementioning
confidence: 99%
“…Efficacy claims have been made for a wide range of nutraceuticals in the CVD prevention and management. The evidence has been summarised in position papers of the International Lipid Expert Panel (ILEP) [11,12,14,15,17]. Amongst the many nutraceuticals with potential lipid-lowering effects, red yeast rice (RYR) stands out as having a particularly broad evidence base, and therefore merits further detailed consideration on its role in lipid disorders management.…”
Section: Lipids Lipoproteins and Atherosclerotic Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…3,77 Research has shown that dyslipidemia leads to the deposition of cholesterol and lipids in blood vessel walls, chronic inflammation, and the formation of atherosclerotic plaques that block blood flow and (when they rupture) lead to acute ischemic attacks. 78 Measures to adjust abnormal lipid metabolism are commonly agreed to prevent the outbreak of CVD. However, many lipid-lowering drugs, such as statins, carry various side effects or contraindications.…”
Section: Therapeutic Potential Psyllium In Cmdsmentioning
confidence: 99%